Tecnica, scrittura e storia nella morfologia di Henri Focillon - Ascari, Pierpaolo (Mechane, 2024)
The article attempts to rethink Henri Focillon’s morphology in the perspective of a footnote that Jacques Derrida dedicated to him in Of Grammatology. From this circumstance, the article derives the possibility of reflecting specifically on the notions of technique and writing.